Chronic osteomyelitis of humerus presenting as scrofuloderma - Susmita Sahu; Satyadarshi Pattnaik; Indrani Mohanty; Moningi Venkata Narasimham; Pritilata Panda (Wolters Kluwer Medknow Publications, 2013)
Scrofuloderma is a common type of cutaneous tuberculosis usually manifests over an infected lymphnode, bone or joint that breaks down to form an undermined ulcer leading to discharging sinuses. We present a case of a 22 year old woman with diffuse swelling of right arm with overlying nodulo ulcerative skin lesions associated with seropurulent discharge. Routine investigations were normal and X-Ray of the right humerus showed the features of chronic osteomyelitis. Smears of the discharge for bacteria, fungi and acid fast bacilli were negative, but culture of skin biopsy showed Mycobacterium tuberculosis which was confirmed by PCR. Histopathology of skin biopsy showed epithelioid granulomatous inflammation suggestive of tuberculosis. After treating the patient with antitubercular therapy complete regression of the lesions occurred.